Home Health Aide Training: An Appeal for Organizational Support. (July 2016) - Palesy, Debra
Abstract : How home healthcare aides (HHAs) adapt their classroom training to their workplaces is central to their own safety and that of their care recipients. A qualitative approach was adopted for this inquiry, where new workers were interviewed in-depth following their classroom training. Findings suggest a perceived lack of supervisor support for classroom training and lack of follow-up in the workplace. Moreover, the need for more peer support was contended, and more comprehensive written materials in clients' homes may also assist workers' learning and enacting safe manual handling techniques in the workplace. The article concludes with recommendations for supporting HHAs' learning, and includes suggestions for future research.